PERBEDAAN ADVERSITY QUOTIENT KEPRIBADIAN AMBIVALENT PENYALAHGUNA NAPZA DI SUMATERA BARAT - Radhiya Nikita Dharma; Rida Yanna Primanita (Jurnal Riset Psikologi, 2019)
This study aims to look at differences in adversity quotient toward ambivalent personality types in drug abuser in West Sumatra. The research design used is quantitative comparative approach. The study population was drug abuser with ambivalent passive, ambivalent active, and ambivalent mixed personality types domiciled in West Sumatra totaling 100 people. The sample collection technique is saturated with a sample of 100 people. This study uses an adversity quotient scale, and the MPTI scale (Milon Personality Test Inventory). The data analysis technique used is one way ANOVA. The results showed that there was no difference in adversity quotient based on ambivalent personality types in drug users in West Sumatra with a value of p = 0.12 (p> 0.05). Meaning even though there are no certain differences in each personality type, but overall there is no difference in adversity quotient for drug abuser in west sumatera. Penelitian ini bertujuan untuk melihat perbedaan adversity quotient berdasarkan tipe kepribadian ambivalent pada penyalahguna NAPZA di Sumatera Barat. Desain penelitian yang digunakan adalah kuantitatif komparatif. Populasi penelitian adalah  penyalahguna NAPZA dengan tipe kepribadian ambivalent pasif, ambivalent aktif, dan ambivalent campuran yang berdomisili di Sumatera Barat berjumlah 100 orang. Teknik pengumpulan sampel menggunakan sampling jenuh dengan jumlah sampel 100 orang. Penelitian ini menggunakan skala adversity quotient, dan skala MPTI (Milon Personality Test Inventory). Teknik analisis data yang digunakan yaitu anova one way. Hasil penelitian menunjukkan tidak terdapat perbedaan adversity quotient berdasarkan tipe kepribadian ambivalen pada penyalahguna NAPZA di Sumatera Barat dengan nilai p = 0,12 (p>0,05). Artinya walaupun terdapat perbedaan tertentu pada tiap tipe kepribadian, namun secara keseluruhan tidak terdapat perbedaan adversity quotient pada penyalahguna NAPZA di Sumatera Barat.